Women Empowerment and Children’s Dietary Diversity in Eastern Uganda - Shimali, Fred; Mangheni, Margaret Najjingo; Sanya, Losira Nasirumbi (Makerere University, 2023)
This study investigated the link between women’s empowerment dimensions and dietary diversity for children in Eastern Uganda, emphasizing the role of empowering women in improving their children’s nutrition. A cross-sectional survey involving 445 households with children aged between six months and five years was conducted in Bugiri and Iganga districts, Eastern Uganda. The project-level women’s empowerment in agriculture index tool (Pro-WEAI) with an add-on module on dietary diversity was used to collect data to measure the different dimensions of women’s empowerment. Dietary diversity was measured through a 24-hour recall method, according to FAO guidelines (2010) for categorizing food groups and generating dietary diversity scores (DDS). Results indicated an average DDS of 5.77, showing medium dietary attainment for children. There is a positive association between women’s control over income and spousal respect, and dietary diversity scores for children. Women with control over income were more likely to provide diverse diets to their children. Social support networks of group membership and autonomy in income also promise to improve diets for children. However, women’s inadequacy in attitudes toward domestic violence and workload were significantly and negatively associated with DDS for children. This study highlights that women’s empowerment plays a vital role in promoting dietary diversity and improving child health. Findings emphasize the need to prioritize interventions that empower women to reduce workload and have control over income to enhance child nutrition, for attainment of the SDGs.